Membaca Gerak Roh di Era Pasca-Kebenaran: Analisis Pneumatologis Video “Propaganda Anti-Islam” Robert Spencer - agustinus daryanto (Institut Filsafat dan Teknologi Kreatif Ledalero, 2022)
This paper aims to show the need to deciphere the movement of the Holy Spirit correctly in the post-truth era, where truth is determined by the dominant system, and not the correct system, as Michel Foucault said.Through the views of Christian pneumatology in both Eastern and Western theological traditions, Asian context, media analysis and philosophy, this paper analyzes anti-Islam propaganda videos by Robert Spencer. The HolySpirit certainly didn’t blow on Spencer’s propaganda, because the Spirit basically unites and not divides (Galatians 5:21-23). In the Pentecost, the Holy Spirit enabled the apostles to be open and accepting differences in language and the aspects contained therein: culture, beliefs, and customs. The pneumatological views of Zizioulas, Jurgen Moltmann, Karl Rahner, Michael Welker, Clark Pinnock, and the Bishops of Asia emphasize that the Holy Spirit who is still moving contains the power that sustains and inspires people towards truth and peace. Hegel’s dialectical philosophy of the Spirit can be a way of thinking for the faithful to critically deciphere the movements of the Spirit through digital literacy. In the digital world, humans as “Hearers of the Word” are “Password Breakers”who are critical in deciphering the movements of the Spirit.Keywords: Holy Spirit, Church, dialogue, post-truth, media